Congenital Secondary Hypothyroidism Evidences in a Dog - Meirelles, Luana da Silva; Moresco, Maurício Bianchini; de Jesus, Luciana; de Carvalho, Guilherme Luiz Carvalho; Ferreira, Márcio Poletto; Pöppl, Álan Gomes (Acta Scientiae Veterinariae, 2017)
Background: Deficiency of thyroid hormones thyroxine (T4) and triiodothyronine (T3) results in multisystemic disease described as hypothyroidism (HpoT). Secondary HpoT is defined by TSH decreased production and, therefore, thyroid hormones. This condition is rare in dogs, accounting for less than 5% of cases. The objective of this report is to describe evidence of congenital secondary hypothyroidism in a mongrel dog and therapeutic response obtained. Case: A 3-year-old neutered male mongrel dog was brought to the veterinarian with a history of overweight without polyphagia, associated with discrete alopecia, poor quality skin and hair coat, lethargy and evident exercise intolerance. Physical examination revealed a body condition score of seven (1 to 9 scale), disqueratosis, pyoderma, ventral cervical alopecia, hair thinning on the posterior surface of the pelvic limbs and nonpalpable thyroid. A body conformation characterized by disproportionate dwarfism was observed. Owners provided a former patient´s X-ray (18 months of age), showing growth plate non-closure in vertebral bodies. Results of a complete blood count (CBC) and serum biochemical profile were within normal limits except for elevated fructosamine (459 µmol/L; reference range: 170-338 µmol/L) and total cholesterol (558 mg/dL; reference range: 135-270 mg/dL). Analyses of the hormone profile showed decreased levels of canine thyroid-stimulating hormone (cTSH) 0.03 ng/mL (reference range: 0.05-0.5 ng/mL), free thyroxine by equilibrium dialysis (fdT4) 0.57 ng/dL (reference range: 0.8-3.0 ng/dL), and total thyroxine (tT4) 5.1 ng/mL (reference range: 15-30 ng/mL). A distal forelimb X-ray was performed and showed opened epiphyseal growth plates from radius and ulnar bones. The patient was discharged with sodium levothyroxine (20 µg/kg PO q 24 hr) until re-evaluation. The patient was re-evaluated 2 months later and clinical symptoms observed at the first admission were still persistent. CBC and serum biochemical profile were within normal range. The values of T4t and cTSH were 21.3 ng/mL (reference range for treated dogs 25-45 ng/mL post-thyroxine) and 0.03 ng/mL respectively. Owners were administering a generic levothyroxine, and then a commercial sodium levothyroxine was prescribed at the same dose for treatment. Clinical improvement was reported by the owner 4 weeks later. A new forelimb and vertebral radiographic examination performed 6 months later revealed complete epiphyseal ossification. Discussion: The patient was diagnosed with central hypothyroidism based on the clinical presentation in conjunction with the laboratory tests results. The main hypothesis argues for a congenital pituitary malformation, leading to a defective hypothalamic-pituitary-thyroid axis function. This decreased hormonal TSH secretion culminated in a chronic mild state of hypothyroidism associated with reduction in the thyroid hormones secretion. Metabolic consequences of mild hypothyroidism affect bone development directly and lead to delayed epiphyseal ossification and epiphyseal growth, reduced long bone growth, and disproportionate dwarfism. Studies have suggested a genetic relation with the development of congenital hypothyroidism, although no disease-causing mutations were found in the genes previously investigated. The prognosis for dogs with secondary hypothyroidism due to malformation or destruction of the pituitary ranges from poor to reserved, with shorter life expectancy in dogs with congenital pituitary malformation due to cysts expansion. Although cost is limiting for some owners, advanced imaging such as computed tomography or magnetic resonance may be useful in the macroscopic evaluation of the pituitary gland and are recommended in central hypothyroidism cases.